One-year outcomes and predictors of mortality after MitraClip therapy in contemporary clinical practice: results from the German transcatheter mitral valve interventions registry - Puls, Miriam; Bekeredjian, Raffi; Senges, Jochen (European heart journal, 2016)
AbstractAims. The transcatheter mitral valve interventions (TRAMI) registry was established in order to assess safety and efficacy of catheter-based mitral val